Comparação de estimativas de perda de solo pela EUPS com produtos de aeronave remotamente pilotada na análise de processos erosivos em áreas de regeneração - Giglio, Luiza Campos (Universidade Federal de São Carlos, 2025)
Erosive processes generate a series of consequences, in addition to physical and chemical degradation of the soil. The Universal Soil Loss Equation (USLE) is normally used to estimate soil loss and to analyze the main factors that contribute to this process. Currently, the use of unmanned aerial vehicles (UAVs), combined with geotechnologies, occurs in several analyses, mainly in environmental monitoring. Thus, the objective of this study was to evaluate the erosive processes in an area with regenerating vegetation to better understand the relevant factors in the erosive process, as well as the importance of vegetation in the recovery of eroded areas, applying the USLE and using photogrammetric products obtained with UAV. Using several data sources, a 62-year temporal analysis was performed with the application of the USLE in the study area, in addition to performing the volumetric analysis of the area affected by erosion using UAV byproducts. As a result, it was observed that the factors of land use and cover, as well as rainfall erodibility, influence the dynamics of erosion the most. Regarding the applied methods, the volume of soil loss obtained by EUPS was higher than the volumetric calculation, especially in areas of vegetation regeneration. Therefore, vegetation and precipitation are the factors that most influence erosion areas, indicating that actions in favor of vegetation recovery are essential to reduce erosion processes.
Comparison of soil loss estimates by EUPS and remotely piloted aircraft products in the analysis of erosion in regeneration areas
Keywords: Erosão; Recuperação ambiental; SIG; RPA; Modelos digitais de elevação; Erosion; Regenerating areas; Digital elevation models; UAV; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS